2020
DOI: 10.1186/s12906-020-2857-1
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin, demethoxycurcumin, and bisdemethoxycurcumin induced caspase-dependent and –independent apoptosis via Smad or Akt signaling pathways in HOS cells

Abstract: Background: Osteosarcoma is the most common primary malignant bone tumor in children and adolescents and has also been associated with a high degree of malignancy and enhanced metastatic capacity. Curcumin (CUR) is well known for its anti-osteosarcoma activity. However, both demethoxycurcumin (DMC), and bisdemethoxycurcumin (BDMC) are natural curcumin analogues/congeners from turmeric whose role in osteosarcoma development remains unknown. Methods: To evaluate the growth inhibitory effects of CUR, DMC and BDMC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 27 publications
1
33
1
Order By: Relevance
“…A previous study [41] has reported that curcuminoids suppress TNF-α-induced NF-κB activation in the order of BDMC < DMC < curcumin. The anti-breast cancer and anti-melanoma activities of BDMC were also less than curcumin and DMC in a cell-based study [42]. Although these investigations exhibited items to the contrary of our study, the superior chemical stability of BDMC over curcumin and DMC could be the reason for the observed stronger anti-adipogenic effect.…”
Section: Discussioncontrasting
confidence: 96%
“…A previous study [41] has reported that curcuminoids suppress TNF-α-induced NF-κB activation in the order of BDMC < DMC < curcumin. The anti-breast cancer and anti-melanoma activities of BDMC were also less than curcumin and DMC in a cell-based study [42]. Although these investigations exhibited items to the contrary of our study, the superior chemical stability of BDMC over curcumin and DMC could be the reason for the observed stronger anti-adipogenic effect.…”
Section: Discussioncontrasting
confidence: 96%
“…The chemical stability is better in bisdemethoxycurcumin than curcumin and demethoxycurcumin. 14 In contrast, demethoxycurcumin has one methoxy group, while curcumin has two methoxy groups. Therefore, the chemical stability is better in demethoxycurcumin than in curcumin.…”
Section: Discussionmentioning
confidence: 99%
“…28 Consistently, methoxy groups of curcumin analogues also played important anti-cancer effects in breast cancer, melanoma, and osteosarcoma. 14 Furthermore, Somparn et al 29 found that methoxy group associated with the antioxidant activity. In our results showed that curcumin, demethoxycurcumin and dimethoxycurcumin displayed the anti-cancer activities such as suppressed cell viability and colony formation in both LN229 and GBM8401 glioma cells.…”
Section: Discussionmentioning
confidence: 99%
“…In year 2020, Huang et al suggested that curcumin and DMC showed better pro-apoptotic effect than BDMC in HOS osteosarcoma cells. 38 Furthermore, it was suggested that phenyl methoxy group may crucially affect direct inhibitory activity on NF-κB 39 . As a direct target of curcumin 40 , the interaction or binding with STAT3.may also be influenced by the presence of phenyl methoxy group, besides of the effect of diketone groups.…”
Section: Discussionmentioning
confidence: 99%